1984
DOI: 10.4049/jimmunol.133.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic analysis of hematopoiesis. III. A hematopoietic progenitor cell surface antigen defined by a monoclonal antibody raised against KG-1a cells.

Abstract: The anti-My-10 mouse monoclonal antibody was raised against the immature human myeloid cell line KG-1a and was selected for nonreactivity with mature human granulocytes. Anti-My-10 immunoprecipitated a KG-1a cell surface protein with an apparent Mr of approximately 115 kD. We describe the binding of this antibody to human hematopoietic cell types and show that My-10 is expressed specifically on immature normal human marrow cells, including hematopoietic progenitor cells. My-10 is also expressed by leukemic mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,005 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…A transmembrane phosphoglycoprotein (CD34) is predominantly regarded as a marker of hematopoietic stem cells (HSC) and hematopoietic progenitor cells. However, it is also established as a marker of other non‐hematopoietic cell types, including vascular endothelial progenitors and embryonic fibroblasts 26,27 . Clinical improvement in response to topical brimonidine tartrate eye drops (0.2%) treatment in the present work was consistent with the histological and immunohistochemical results.…”
Section: Discussionsupporting
confidence: 88%
“…A transmembrane phosphoglycoprotein (CD34) is predominantly regarded as a marker of hematopoietic stem cells (HSC) and hematopoietic progenitor cells. However, it is also established as a marker of other non‐hematopoietic cell types, including vascular endothelial progenitors and embryonic fibroblasts 26,27 . Clinical improvement in response to topical brimonidine tartrate eye drops (0.2%) treatment in the present work was consistent with the histological and immunohistochemical results.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, we found that genes involved in positive regulation of differentiation were upregulated in T-ALL cells following treatment with bardoxolone methyl or omaveloxolone. Since the hematopoietic progenitor marker CD34 ( 51 ) was downregulated by both OTs and MYB knockdown, this suggests that the differentiation seen following OT treatment is, at least partly, mediated by decreased MYB expression in T-ALL cells. This conclusion is further supported by studies showing that MYB expression is high in immature and progenitor-like cells and suppress differentiation of both normal and leukemic cells ( 7 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, two sub-clusters of candidate articular cartilage progenitors featured by Cd34 or Ly6e / Ly6a were discovered. Cd34 was first described on hematopoietic stem and progenitor cells, 111 and recently, considerable studies have demonstrated that Cd34 is expressed by a multitude of other non-hematopoietic cell types including fibrogenic/adipogenic progenitors, 112 muscle satellite cells, 113 corneal keratocytes, interstitial cells, epithelial progenitors, and vascular endothelial progenitors. 114 It shows that Cd34 + cells discovered in various tissues are usually characterized with enhanced progenitor features.…”
Section: Discussionmentioning
confidence: 99%